Pengaruh Beban Kerja, Disiplin Kerja, dan Lingkungan Kerja Terhadap Kinerja pada Pegawai Kantor Kecamatan Tarokan - Rochmatul Hidhayah Siti Mualiyah; Bambang Suwarsono; Brahma Wahyu (Jurnal Riset dan Inovasi Manajemen, 2025)
This study aims to analyze the influence of workload, work discipline, and the work environment on employee performance at the Tarokan District Office. Employee performance is a crucial element in achieving organizational objectives, as human resources are considered the most valuable asset of an institution. Workload, work discipline, and the work environment are three interrelated factors that often determine whether employees can achieve optimal performance levels. This research employs a quantitative approach with data collected through questionnaires distributed to employees of the Tarokan District Office. The analysis was conducted to examine both partial and simultaneous effects of the three variables on employee performance. The findings reveal that workload partially has a significant effect on employee performance, indicating that a balanced workload improves effectiveness while excessive workload may hinder output. Similarly, work discipline partially demonstrates a significant effect, highlighting the role of adherence to rules and punctuality in enhancing performance outcomes. The work environment also partially exerts a significant effect, suggesting that supportive facilities, comfortable conditions, and positive interpersonal relationships contribute to higher productivity. Furthermore, the results show that workload, work discipline, and work environment simultaneously have a significant effect on employee performance. These findings provide important implications for organizational leaders in designing policies that ensure sustainable performance improvements.